Influencing Human Interaction Eleven Years With IPR - Kagan, Norman ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
The author describes an instructional film program for counselors-in-training that employs a teaching strategy based on the principle of counselor therapist developmental tasks. The tasks are specific enough for the majority of students to grasp the concept or learn the skills, yet are not so finite as to be of dubious relevance to the complex dynamic behavior of counselor or therapist as a positive influence in human interaction. The general teaching strategy to implement the tasks has evolved as a sequential progression of lessons beginning with a didactic presentation of concepts, followed by simulation exercises, interpersonal affective stress, video and physiological feedback, study of self in-action, feedback from clients and, finally, understanding of and skill at dealing with the complex bilateral impacts which occur when two people are in relationship with each other; in general, from specific skills to complex interaction, and from low to high anxiety tasks. (Author/RWP)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Counselor Training; Developmental Tasks; Graduate Students; Instructional Films; Interaction Process Analysis; Interpersonal Relationship; Methods Research; Program Descriptions; Teaching Methods; Interpersonal Process Recall